Innovate or perish : managing the enduring technology company in the global market - Kahn, Edward (Edward A.) (Wiley, 2007)
Praise for Innovate or Perish Managing the Enduring Technology Company in the Global Market. ''Successful innovation calls for negotiating value-creating, sustainable agreements across various forms of IP, technologies, companies, and even industries and countries.